Elevated propionate and its association with neurological dysfunctions in propionic acidemia - Chen, Xiaoxin; Cheng, Qing; Zhang, Guo-Fang (Frontiers in Molecular Neuroscience, 2025)
Propionate, a short-chain fatty acid (SCFA), has recently attracted attention for its various health benefits. However, elevated levels of propionate in certain pathological conditions can have adverse effects. Propionic acidemia (PA) is a rare metabolic disorder caused by mutations in the propionyl-CoA carboxylase (PCC) gene (PCCA or PCCB), leading to reduced PCC activity and impaired propionyl-CoA metabolism. This metabolic block at the PCC-mediated step results in the accumulation of propionyl-CoA and its metabolites, including propionate, contributing to various complications, such as neurological dysfunction, in patients with PA. This review examines propionate synthesis, its physiological role, its metabolism in healthy individuals and those with PA, and the pathological link between elevated propionate levels and neurological dysfunctions in PA patients. A deeper understanding of propionate metabolism under both normal and pathological conditions will help clarify the full spectrum of its metabolic effects.